ANALISIS TINGKAT EFISIENSI PENERIMAAN PAJAK DAERAH DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH PADA TAHUN 2016-2020 DI KABUPATEN PURWOREJO - Nur Atika; Agustina Prativi Nugraheni (Transpublika Publisher, 2024)
Regional development is the independence of a region which is an inseparable part of the success of policies decided by the government. In the state revenue and expenditure budget (APBN), the most significant state revenue target is obtained from the taxation sector. The taxation sector contributes significantly to a country's revenue and can be relied upon as financing for government development, especially regional development. The research was conducted with the aim of analyzing how much the rate of development and the level of effectiveness of local tax revenues in increasing Regional Original Revenue (PAD) in Purworejo Regency. The data used is data on local taxes and local revenue of Purworejo Regency for a period of 5 years, namely 2016-2020 obtained from BPKPAD Purworejo Regency. The data analysis used in this research is quantitative descriptive method. The results showed that the average development rate of local revenue was 18.04% and the average effectiveness rate of local tax revenue was 125.112%, indicating that the local tax revenue of Purworejo Regency was categorized or classified as very effective, so that the local government of Purworejo Regency needed to increase supervision, guidance and evaluation of local tax collection because it had made a large contribution to the local revenue of Purworejo Regency.